Constituents of the Essential Oil from the Flower, Leaf and Stem of Salvia viridis L. Grown in Turkey - Yayli, Nuran; B. Cansu, Tayyibe; Yilmaz, Nagihan; Yasar, Ahmet; M. Cetin, Muhammet; Yayli, Nurettin (Asian Journal of Chemistry, 2010)
The essential oil of Salvia viridis L. (Lamiaceae) was prepared by hydrodistillation of flower, leaf and stem and characterized by GC and GC-MS. A total of 53, 66 and 35 compounds were identified, constituting over 96.5, 96.4 and 88.5 % of oil composition of the flower, leaf and stem of S. viridis, respectively. Sesquiterpene hydrocarbons were shown to be the main group of constituents (in flower: 52.8 %, in leaf: 50.2 %, in stem: 48.7 %). The major components of the oils of S. viridis were β-pinene (leaf, 26.4 %), trans-muurola-4(14),5-diene (flower, 18.5 %) and germacrene D (stem, 16.0 %). Flower and leaf parts of the oils were rich in terpenoid constituents in the total ratio of 96.3 % in flower, 94.9 % in leaf and stem oil of S. viridis had less terpenoids (72.6 %).